1972
DOI: 10.1130/mem135-p95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cohesion and Granularity on Deformational Behavior of Anisotropic Rock

Abstract: Triaxial compression tests were run on seven orientations of three rocks with pervasive planar anisotropy-slate, phyllite, and schist-to evaluate the effects of cohesion and granularity on anisotropic strength variation and deformational mode. The rocks show a gradation in the percentage of platy minerals, and in the size, shape, and percentage of quartz grains present. Experiments were carried out at confining pressures of 500, 1,000, and 2,000 bars, and all tests were duplicated. The tests on slate were dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…8a: Donath's 1972 data on phyllite; Fig. 8b: Niandou et al 1997 data for shale), has been observed in relatively compact rocks such as slate, phyllite, and schist (Donath 1972;Nasseri et al 1997), and gneiss and amphibolite (Vernik et al 1992a), as well as a porous rock such as shale (McLamore & Gray 1967;Niandou et al 1997).…”
Section: Influence Of Foliation On Development Of Dilatancy and Brittmentioning
confidence: 93%
See 1 more Smart Citation
“…8a: Donath's 1972 data on phyllite; Fig. 8b: Niandou et al 1997 data for shale), has been observed in relatively compact rocks such as slate, phyllite, and schist (Donath 1972;Nasseri et al 1997), and gneiss and amphibolite (Vernik et al 1992a), as well as a porous rock such as shale (McLamore & Gray 1967;Niandou et al 1997).…”
Section: Influence Of Foliation On Development Of Dilatancy and Brittmentioning
confidence: 93%
“…(a) Peak stress as a function of bedding angle /3 for selected data on phyllite fromDonath (1972). (b) Peak stress as a function of bedding angle/3 for selected data on shale from Niandou et al(1997).…”
mentioning
confidence: 99%
“…4); this must therefore be considered an absolute weakening mechanism. In order to assess the level of mechanical anisotropy that may be expected due to a foliation marked by phyllosilicates, we have reviewed data published in several papers reporting on triaxial tests (Donath 1961(Donath , 1972Walsh & Brace 1964;Attewell & Sandford 1974;McCabe & Koerner 1975;Bell & Coulthard 1997;Duveau et al 1998) and direct shear tests (Collettini et al 2009). Triaxial tests were performed changing systematically the orientation of foliation with respect to the imposed s 1 axis from 08 to 908.…”
Section: The Sprechenstein-mules Fault Zonementioning
confidence: 99%
“…Even if a direct link between kink band geometry and palaeostress is assumed, the question can be raised whether the pre-existing local anisotropy may have influenced the (far-field) stress directions (cf. Zandvliet, 1960;Ramsay, 1962;Cobbold et al, 1971;Donath, 1972;Murphy, 1988;Konopasek et al, 2001). This is examined by means of an analysis of contractional kink bands from two slate belts in which the orientation of the main, kinked anisotropy gradually changes on a scale exceeding that of the kink bands.…”
Section: Introductionmentioning
confidence: 99%